Socioeconomic inequality in the worsening of psychosocial wellbeing via disrupted social conditions during COVID-19 among adolescents in Hong Kong: self-resilience matters - Chung, Gary Ka-Ki; Chan, Yat-Hang; Lee, Thomas Sze-Kit; Chan, Siu-Ming; Chen, Ji-Kang; Wong, Hung; Chung, Roger Yat-Nork; Ho, Esther Sui-Chu (Frontiers in Public Health, 2023)
Background Adolescents, especially the socioeconomically disadvantaged, are facing devastating psychosocial impact of the COVID-19 pandemic during their critical developmental period. This study aims to (i) examine the socioeconomic patterning of the worsening of psychosocial wellbeing, (ii) delineate the underlying mediating factors (i.e., overall worry about COVID-19, family's financial difficulty, learning problems, and loneliness), and (iii) explore the moderating effect of resilience in the inter-relationship among adolescents under COVID-19. Methods Based on maximum variation sampling of 12 secondary schools of diverse socioeconomic background in Hong Kong, 1018 students aged 14-16 years were recruited and completed the online survey between September and October 2021. Multi-group structural equation modeling (SEM) by resilience levels was employed to delineate the pathways between socioeconomic position and the worsening of psychosocial wellbeing. Results SEM analysis showed a significant total effect of socioeconomic ladder with the worsening of psychosocial wellbeing during the pandemic in the overall sample (β = −0.149 [95% CI = −0.217 – −0.081], p < 0.001), which operated indirectly through learning problems and loneliness (both p < 0.001 for their indirect effects). Consistent pattern with stronger effect size was observed in the lower resilience group; nonetheless, the associations were substantially mitigated in the higher resilience group. Conclusion In addition to facilitating self-directed learning and easing loneliness during the pandemic, evidence-based strategies to build up resilience among adolescents are critical to buffer against the adverse socioeconomic and psychosocial impacts of the pandemic or other potential catastrophic events in the future.